Fulfillment of Wife's Financial Support by Husband with Prisoner Status at Pangkalan Bun Class IIB Prison - Eliyana Septiyani; Maimunah; Anas Maulana (Al-Bayyinah, 2026)
The fulfillment of a wife's maintenance by a husband serving a prison sentence presents complex legal and social challenges due to limited access to productive work within correctional institutions. This study aims to analyze the legal standing of a husband's obligation to provide financial support under Islamic law and Indonesian positive law, examine the empirical reality of its fulfillment at the Pangkalan Bun Class IIB Correctional Institution, and identify alternative mechanisms to protect the economic rights of wives during the period of incarceration. Employing an empirical legal method with a socio-legal approach, data were gathered through in-depth interviews with prisoners' wives, family members, and correctional officers, supported by a comprehensive review of relevant legal sources. The findings indicate that while the financial obligation remains legally binding, it cannot be effectively fulfilled because inmates' work programs are predominantly rehabilitative and generate minimal income. Consequently, this study reveals a social dynamic where the financial needs of the wives are shifted to and borne by the extended family, reflecting a strong sense of social solidarity. The novelty of this research lies in its identification of the husband's family as a de facto economic protection mechanism at the local level, emerging as an alternative solution when formal legal systems fail to guarantee wives' economic rights due to structural constraints within the correctional system.